Involving behavioral scientists, health care providers, and HIV-infected patients as collaborators in theory-based HIV prevention and antiretroviral adherence interventions. - Fisher, Jeffrey D; Cornman, Deborah H; Norton, Wynne E; Fisher, William A (Journal of acquired immune deficiency syndromes (1999), 2006)
Health care providers are often hesitant to attempt health behavior change interventions with patients, although such interventions are frequently needed. When provider-initiated health behavior change interventions are attempted, they are often based on intuition or consist solely of delivering information and are insufficient to change behavior, rather than being based on well-validated and effective behavior change models. We argue that provider-initiated health behavior change interventions are effective and efficient if they are based on appropriate empirically validated theoretical models and developed in collaboration with behavioral scientists and patients. We present a new model for developing such collaborative interventions and initial evidence for its success.
Keywords: Anti-HIV Agents; Behavioral Sciences; Consensus; Health Knowledge, Attitudes, Practice; Health Personnel; HIV Infections; Humans; Patient Compliance